Pengaruh Store Atmosphere Dan Harga Terhadap Keputusan Pembelian Minyak Goreng Fortune Di Supermarket Sinar Terang Kota Probolinggo - Diantoro, Ainul Yaqin; Tyas, Yayuk Indah Wahyuning; Haidiputri, Trivosa Aprilia Novadiani (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
There are many aspects that a customer considers when choosing a product, for example the existing store atmosphere and price. Every time you build a company, generally all companies want to be successful in running their business. The type of research used is descriptive quantitative with a causal associative approach, with the independent (free) variables Store Atmosphere (X1) and Price (X2) and the dependent (bound) variable Purchase Decision (Y). The population used in this research is consumers. Determining the number of respondents (sample) used was nonprobability sampling. Data sources include: (1) primary data, (2) secondary data. The data analysis methods used include: validity and reliability tests, classical assumption tests, multiple linear regression analysis, coefficient of determination (R square), and hypothesis testing consisting of the t test and F test. Research results from the simultaneous store atmosphere test (X1 ) and Price (X2) have a significant effect on purchasing decisions (Y) from the F test calculation, obtained Fcount = 272.241. Apart from that, the partial test shows that store atmosphere (X1) has a significant influence on purchasing decisions (Y) with a tcount = 3.849 and price (X2) has a significant influence on purchasing decisions (Y) with a tcount = 17.151.